2016
DOI: 10.1038/srep35295
|View full text |Cite
|
Sign up to set email alerts
|

Testing the relationship between mimicry, trust and rapport in virtual reality conversations

Abstract: People mimic each other’s actions and postures during everyday interactions. It is widely believed this mimicry acts as a social glue, leading to increased rapport. We present two studies using virtual reality to rigorously test this hypothesis. In Study 1, 50 participants interacted with two avatars who either mimicked their head and torso movements at a 1 or 3 second time delay or did not mimic, and rated feelings of rapport and trust toward the avatars. Rapport was higher towards mimicking avatars, with no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 59 publications
(105 reference statements)
1
49
1
Order By: Relevance
“…For instance, knowing the participant's head location means that a virtual character can be programmed to orient their head and/or gaze towards participant's head (Forbes, Pan, & Hamilton, 2016; Pan & Hamilton, 2015) and to maintain an appropriate social distance by stepping back or forward (Pan, Gillies, Barker, Clark, & Slater, 2012). The ability to link the behaviour of a virtual character to the participant in real time also facilitated a series of studies on mimicry in VR, where the virtual character copies participants’ head movements (Bailenson & Yee, 2007; Verberne, Ham, Ponnada, & Midden, 2013), or both head and torso movements (Hale & Hamilton, 2016). …”
Section: The Foothills – How To Use Vrmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, knowing the participant's head location means that a virtual character can be programmed to orient their head and/or gaze towards participant's head (Forbes, Pan, & Hamilton, 2016; Pan & Hamilton, 2015) and to maintain an appropriate social distance by stepping back or forward (Pan, Gillies, Barker, Clark, & Slater, 2012). The ability to link the behaviour of a virtual character to the participant in real time also facilitated a series of studies on mimicry in VR, where the virtual character copies participants’ head movements (Bailenson & Yee, 2007; Verberne, Ham, Ponnada, & Midden, 2013), or both head and torso movements (Hale & Hamilton, 2016). …”
Section: The Foothills – How To Use Vrmentioning
confidence: 99%
“…how accurately etc.? By building a VR system which implements mimicry, we can begin to address these questions and test the theory in detail (Hale & Hamilton, 2016). Similarly, theories might suggest that joint attention is implemented in particular brain systems, but testing this required a VR implementation of joint attention (Schilbach et al ., 2010), which requires us to specify the duration of mutual gaze between the participant and VC, the timing of the looks to the object, and the contingencies between these behaviours.…”
Section: The Munros – Challenges In the Implementation Of Vrmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study suggested that mimicry makes avatars more likely to be trusted [49]. However, these results have not been consistently replicated [28,46]. This paper sets out to investigate this apparent inconsistency in the results.…”
Section: Introductionmentioning
confidence: 92%
“…Our more refined metrics could be used not simply to match communications media to communicative task, but also to design VR with greater presence. Meetings held in a VR environment could benefit from the medium's ability to transmit nonverbal channels of communication, especially if those channels were modeled with spatiotemporal fidelity rather than as categories like "head and torso movements" (Hale & Hamilton, 2016). It might be tempting to capture and algorithmically distill those cues as a visible bar or heat map, but such a process would suffer serious information losses during both encoding and decoding.…”
Section: A Note On Physical Media and Alternate Realitiesmentioning
confidence: 99%